2000
DOI: 10.1038/82430
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco ribosomal DNA spacer element stimulates amplification and expression of heterologous genes

Abstract: Here we show that the cis-acting genetic element aps (amplification-promoting sequence), isolated from the nontranscribed spacer region of tobacco ribosomal DNA (rDNA), increases the level of expression of recombinant proteins. Transgenic tobacco plants, transformed with expression cassettes containing the herbicide-resistant acetolactate synthase (hr-ALS) gene or the green fluorescent protein (GFP) gene fused to the aps sequence, had greater levels of corresponding messenger RNAs (mRNAs) and proteins compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…1C). It was previously reported that the presence of aps could be associated with 2-5-fold increase in the copy number of transgenic genes (Borisjuk et al, 2000). Similarly, as revealed in our study by comparative southern hybridization, the transformants with aps (line RM3, RM7 and RM8) seemed to contain many more multiple copies.…”
Section: Molecular Characterization Of Transgenic Plantssupporting
confidence: 87%
See 3 more Smart Citations
“…1C). It was previously reported that the presence of aps could be associated with 2-5-fold increase in the copy number of transgenic genes (Borisjuk et al, 2000). Similarly, as revealed in our study by comparative southern hybridization, the transformants with aps (line RM3, RM7 and RM8) seemed to contain many more multiple copies.…”
Section: Molecular Characterization Of Transgenic Plantssupporting
confidence: 87%
“…Although the gene copy number is not always proportional to the mRNA expression level due to positional affect, methylation, and partial gene silencing, etc (Meyer and Saedler, 1996;Stam et al, 1998), our results from Southern blot and RT-PCR analysis suggested that aps is likely to promote transgenic expression by increasing both the target gene copy number and the transcription level in rice, similar to its effects previously reported in tobacco and tomato. Moreover, Borisjuk et al (2000) demonstrated the effects of aps on the increase in the transgene copy number and the enhanced expression could be stably inherited in the progeny of the transgenic tobacco. Further experiments in our future study are still needed to observe if the offspring of transgenic rice carrying multiple copies of the Acrp30 gene would stably retain a high level of expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Damage to rDNA might therefore be particularly prone to set off a repair cascade. Whatever the proximate trigger, different genetic elements have been identified which seem to facilitate rapid amplification either in cis (Borisjuk et al, 2000) or in trans (Lohe and Roberts, 1990). This sort of expansion could potentially lead to very rapid changes in rDNA sequence composition within populations.…”
Section: Recolonisation After the Last Glacial Maximummentioning
confidence: 99%